Implicaciones de la alimentación continua sobre la demanda de oxígeno en un pez agástrico con intestino corto (Teleostei: Atherinopsidae) - Fonseca-Madrigal, Jorge; Martínez-Chávez, C. Cristian; Ríos-Durán, María Gisela; Mariño-Reyes, Laura; Martínez Palacios, Carlos (Ecosistemas y Recursos Agropecuarios, 2024)
Continuous illumination and increased feeding periods have enhanced growth in commercial fish species. However, oxygen consumption under these conditions has yet to be previously assessed in agastric short-intestine fish. This study evaluated Chirostoma estor (Atherinopsidae) oxygen consumption under three specific feeding and light regimes: resting-unfed, routine-fed, and continuous light/feeding. Fish in the continuous light/feeding condition presented oxygen consumption levels 60 and 20% higher than resting-unfed and routine-fed fish, respectively. The latter implies that constant high oxygen supply levels are required to satisfy the demand for C. estor raised under these high growth rate conditions. The present study shows the relevance of determining oxygen consumption levels during continuous illumination and extended feeding periods to consider optimal oxygen levels required to achieve better performance indicators, such as the growth and welfare of atherinopsids and species with similar digestive configurations.
Keywords: Chirostoma estor; Continuous illumination; Frequent feeding